2020
DOI: 10.21203/rs.3.rs-18209/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prognostic prediction model for glioblastoma: a metabolic gene signature and independent external validation

Abstract: Background. Glioblastoma (GBM) is the most common primary malignant intracranial tumor and is closely related to metabolic alterations. However, few accepted prognostic models are currently available, especially models based on metabolic genes. Methods . Transcriptome data were obtained for all patients diagnosed with GBM from the Gene Expression Omnibus (GEO) (training cohort, n=369) and The Cancer Genome Atlas (TCGA) (validation cohort, n=152) with the following variables: age at diagnosis, sex, follow-up an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…The study of Lei et al . showed 341 metabolic genes that exhibited significant differences between normal brain and GBM tissues, and they constructed a prognostic prediction model for GBM according to these metabolic genes 20 . Johansen and colleagues further found that GBM displayed distinct sex‐based differential methylation patterns based on molecular subtype 21 …”
Section: Introductionmentioning
confidence: 99%
“…The study of Lei et al . showed 341 metabolic genes that exhibited significant differences between normal brain and GBM tissues, and they constructed a prognostic prediction model for GBM according to these metabolic genes 20 . Johansen and colleagues further found that GBM displayed distinct sex‐based differential methylation patterns based on molecular subtype 21 …”
Section: Introductionmentioning
confidence: 99%